Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada Pengelola Gedung Plaza BNI Tangerang Selatan - Fitri Sabina; Ali Zaenal Abidin; Juwita Ramadani Fitria; Guruh Dwi Pratama (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Employee performance is a critical factor in achieving organizational goals, and it is influenced by various factors, including work motivation and job satisfaction. In modern organizational management, particularly in service-oriented sectors, understanding the drivers of employee performance is essential to maintain efficiency, productivity, and service quality. This study aims to examine the effect of work motivation and job satisfaction on employee performance at the BNI Plaza Building Management, both partially and simultaneously. A quantitative approach with a survey method was employed. The research was conducted at BNI Plaza, Tangerang Selatan, involving 95 employees as respondents using a census sampling technique. Data were collected through structured questionnaires distributed via WhatsApp, using a closed-ended Likert scale. The collected data were processed and analyzed using SPSS 26 with multiple linear regression analysis. The study included descriptive analysis, validity and reliability testing, classical assumption testing, and hypothesis testing. The results indicate that both work motivation and job satisfaction have a significant positive effect on employee performance. High levels of motivation and satisfaction contribute to improved productivity, work discipline, and overall quality of work. However, other factors, such as leadership style, organizational culture, and work environment, also play a role and warrant further investigation. These findings imply that management should not only enhance motivation and satisfaction but also consider other organizational factors to optimize employee performance sustainably.